The Effect of Laboratory-Based Blended-Project Based Learning Model on The Science Process Skills of Students - Nurdiansah, Ihsan; Surahman, Endang; Makiyah, Yanti Sofi; Kurnia, Elis (Department of Physics, Faculty of Mathematics and Natural Sciences, 2024)
The process of learning science, especially physics, has often had problems. The problem that often arises so far in the field is how to teach teachers who still use conventional methods. This learning method has not been able to support the science learning process, which causes low science process skills in students. The purpose of this study was to determine the effect of the laboratory-based Blended-Project Based Learning (B-PjBL) model on students' science process skills. The research method used was quasi-experimental with a posttest control group design. The results of the hypothesis test using the t-test showed that the laboratory-based B-PjBL model has a positive effect on students' science process skills.